PENGARUH PERMAINAN FLASHCARD TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 5-6 TAHUN DI TK PERTIWI KOTA PEKANBARU - Dini, Rahmi Permata; N, Zulkifli; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is based on the observations of researchers at TK Pertiwi Pekanbaru City on the ability to recognize the concept of child numbers not yet developing optimally. So research needs to be done to optimize the ability to recognize the concept of numbers using flashcard game media. The purpose of this study was to determine the effect of flashcard playing media on the ability to recognize the number concepts of children aged 5-6 years. The study used an experimental method with one group pre-test post-test design design with a sample of 20 children. Data collection technique is observation with an observation sheet. The data analysis technique used the t-test using I.BM SPSS statistical ver 20. From the results of data analysis, it was obtained that the tcount was 4.507, greater than ttable = 2.093 with sig 0.000 < 0.05. So, it can be concluded that there is an influence of the flashcard media on the ability to recognize the number concept of children aged 5-6 years at TK Pertiwi Pekanbaru City by 16.06%. Key Words: Flashcard Media, Number Concepts, Children Aged 5-6 Years